La salle de classe et le discours de l'enseignant - Wanderley C. Oliveira (Nantes Université, 2018)
We have identified with H. Arendt (1993) rhetoric as a specific mode of the political discourse, whereas dialectic comes as an appropriate mode to the philosophical discourse. Rhetoric aims at persuasion. There the objective is to impose someone's point of view over that of someone else. With dialectic what is aimed at is to discuss something with someone. While rhetoric brings up power of some over others, dialetic favours friendship. Between these two modes of discourse, which should the teacher's discourse favour in the classroom? To reach some conclusion, we first characterize rhetoric and dialectic. Then we prepare a table comparing them. Last but not least, we endeavour to realize what may happen when we attach these to the teacher's discourse. The rhetoric teacher's discourse, although helpful in the learning process, aims at, ultimately, the exercise of power. Hence the importance of a slight use of irony as a resource to look askance at rhetoric in favour of dialectic which, instead of a relation of power, creates friendship, based on respect and trust of one in the other.